Seasonal Changes in Body Composition, Jump, Sprint, and Agility Performance Among Elite Female Handball Players - Stanković, Mima; Katanić Borko; Govindasamy Karuppasamy; Badau Adela; Badau Dana; Masanovic Bojan; Bojić Ivana (Applied Sciences, 2025)
Assessing physical fitness throughout the entire season can provide valuable insights for designing effective training programs to enhance handball performance. Therefore, the aim of this study was to investigate seasonal changes in body composition, jump, sprint, and agility performance among elite female handball players. This study involved fourteen elite female handball players (age 21.98 ± 1.22) who participated in the Serbian Handball Super League and the European Handball Federation (EHF) European Cup during the 2022/23 season. Within the framework of seasonal changes, five measurements were made. Players were tested for height, weight, BMI, body fat and muscle mass percentage, jump performance (CMJ, CMJA, SJ, CMJ right, CMJ left), linear sprint (5 m, 10 m, 20 m), and agility performance (zig-zag and slalom). Repeated measures ANOVA revealed no changes in body composition parameters during the season. Among the five jump performance tests, a significant change was observed only in the CMJ left test, where better values were achieved in the fourth and fifth measurements compared to the initial measurement. In sprints over 5 and 10 m, significant changes were noted between specific measurement points, while no differences were observed in the 30-m sprint. For agility, differences were recorded in four out of five tests, with the best performances in the Zig-Zag tests observed in the third measurement, while in other tests, the best results were most often recorded in the second and fifth measurements. These results indicate that body composition remained stable, while performance improvements were specific to certain physical capacities and time points during the season. These findings can help coaches design targeted strength and agility training aligned with key performance periods, emphasizing short sprints and agility with/without the ball, rather than focusing on body composition changes. However, this study is limited by its small sample size and single-season scope, which may affect the generalizability of the results.
Keywords: seasonal variation; body fat; muscle mass; physical fitness; women’s handball players